FREQUENCY ADJUSTMENT OF WELL PUMPING EQUIPMENT - Maxmudov, Bekzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. improve energy efficiency by adjusting the frequency of well pumping equipment. Methods. Frequency adjustment, thermal image management, analytical analysis, energy-efficient operating modes of pumps, reliability indicators. Results. Based on equations (1) - (42) in the MatLab/Simulink program, the simulation model of the "Autonomous voltage inverter - asynchronous electric motor with a short-circuited rotor - centrifugal pump" system was developed. Conclusion. This computer model confirmed the hypothesis that it is possible to reduce the energy consumption of the well pumping system by adjusting the rotation frequency of the electric motor rotor by adjusting the supply frequency in scalar systems of frequency converters at the same mains frequency..